Microencapsulated propolis in chewing gum production - Bostancı, Emre; Gölge, Evren (Emirates Journal of Food and Agriculture, 2023)
Propolis is a resin with high antibacterial and antioxidant properties that honey bees (Apis mellifera L.) gather and then harmonize through their metabolic secretions. Propolis is beneficial to dental health because it contains antibacterial activity against the Streptococcus mutans, which causes tooth decay. The aim of this study is to use microencapculated propolis extract (MPE) in chewing gum formulation for the first time, in order to protect propolis from environmental effects during production and to ensure controlled release in mouth. Spray drying method was applied where maltodextrin acted as coating material. The particle structure of MPE was investigated by scanning electron microscope. The encapsulation efficiency was determined as 62.19%. The hygroscopicity and moisture content of the MPE particles was found as 31.50% and 7.98% respectively. The DPPH scavenging ability, total flavonoid and total phenolic content of the MPE appeared lower than propolis extract. The total flavonoid content of MPE was calculated as 29.06 mg/kg and total phenolic content as 89.17 mg/kg. In vitro antimicrobial activity against Streptococcus mutans of 9% MPE containing gum samples was measured highest with 4.20 mm zone diameter. Hunter b* value increased with increasing MPE concentration. The final MPE incorporated chewing gum appear to be highly functional. Keywords: Propolis; Spray drying; Chewing gum; Functional food